Lembaga Penjaminan Mutu Pendidikan Aceh dan Peningkatan Mutu Guru Pendidikan Agama Islam - Mulyadi M. Ramli (Tadabbur: Jurnal Peradaban Islam, 2021)
One of the institutions tasked with helping to improve the quality of education is the Education Quality Assurance Institution (LPMP). The purpose of this study was to identify the role of the Education Quality Assurance Institution in improving the quality of Islamic Religious Education (PAI) teachers. This study uses a qualitative approach, this approach was chosen based on the research objective, namely to describe and analyze the process of improving the quality of PAI teachers in Suka Makmur District carried out by LPMP Aceh. The data collection techniques are interviews, and document studies. The results showed that the role of LPMP Aceh was as an organizer in the development of the education quality assurance system program, as a facilitator in education and training, and as a companion for education and training in improving the competence of PAI teachers. The form of coordination of the PAI Teacher Quality Improvement Program at LPMP Aceh in collaboration with Educational Institutions/Departments by providing technical assistance to the Education Office, and collaboration with KKG/MGMP teacher groups through mentoring in schools. As for the control that Aceh's LPMP faces is less coordinated the recorded retention schedule that Aceh's LPMP itself or outside the LPMP, and the allocation of the recorded funds also constitutes control because it is not in the List of Budget Project DIPA LPMP Aceh.